2014
DOI: 10.2147/cia.s61934
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aging on medial olivocochlear system function

Abstract: BackgroundThere is still controversy regarding the influence of aging on medial olivocochlear (MOC) system function. The main objective of this study is to measure age-related changes of MOC system function in people with normal hearing thresholds.MethodBilateral assessment of the MOC effect for click-evoked otoacoustic emissions (CEOAEs; at 70±3 dB peak sound pressure level [pSPL], click at 50/second, 260 repeats, 2.5–20 millisecond window) and for distortion product otoacoustic emissions (DPOAEs; with [frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 38 publications
4
18
0
1
Order By: Relevance
“…Clinical populations, such as hearing-impaired individuals, often experience significant difficulties communicating in background noise. It has been suggested that some hearing-in-noise problems could be due at least in part to compromised MOC function (Keppler et al, 2010;Lisowska et al, 2014). However, little is known about how the MOC system functions in ears with hearing loss, primarily due to methodologic barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical populations, such as hearing-impaired individuals, often experience significant difficulties communicating in background noise. It has been suggested that some hearing-in-noise problems could be due at least in part to compromised MOC function (Keppler et al, 2010;Lisowska et al, 2014). However, little is known about how the MOC system functions in ears with hearing loss, primarily due to methodologic barriers.…”
Section: Introductionmentioning
confidence: 99%
“…aus der psychosozialen Situation der Betroffenen heraus. Studien zeigen Veränderungen otoakustischer Emissionen mit steigendem Lebensalter, welche über eine im efferenten medialen olivocochleären System nachlassende Wirkung acetylcholinerger Hemmung erklärt wird [51,52]. In Tiermodellen wurde gezeigt, dass inhibitorische Mechanismen in den auditorischen Gehirngebieten durch akustische Traumata und mit steigendem Alter geschwächt werden [10,51,53].…”
Section: Statistische Auswertungunclassified
“…It might be argued that the effect exists, but that the current procedure is not sensitive enough to detect it. However we reiterate that very strict criteria were used (SNR >12 dB), much higher than in standard measurements (e.g., SNR >3 or >6 dB, Mishra & Lutman, 2013 ; Lisowska et al, 2014 ; Micarelli et al, 2016 ; Killan et al, 2017 ). Another reason for seeing no effect might be because all TEOAE parameters, and especially contralateral suppression effects on TEOAEs, have high variability, even when refitting of the probe is avoided ( Mishra & Lutman, 2013 ; Stuart & Cobb, 2015 ; Jedrzejczak et al, 2016 ).…”
Section: Discussionmentioning
confidence: 95%